Association between Insulin-Like Growth Factor-1 and Uric Acid in Chinese Children and Adolescents with Idiopathic Short Stature: A Cross-Sectional Study. (28th January 2018) - Wang, Panpan; Ji, Baolan; Shao, Qian; Zhang, Mei; Ban, Bo
Abstract : Objective . The aim of this study was to examine the relationship between insulin-like growth factor-1 (IGF-1) and serum uric acid (UA) in Chinese children and adolescents with idiopathic short stature (ISS). Methods . A cross-sectional study of 91 Chinese children and adolescents with ISS was performed. Anthropometric measurements and biochemical parameters were tested. The standard deviation score of IGF-1 (IGF-1 SDS) was calculated. Results . A univariate analysis displayed a significant positive correlation between IGF-1 SDS and UA (P = 0.004 ). In multivariate piecewise linear regression, the levels of IGF-1 SDS increased with the elevation of UA when UA was between 168  μ mol/L and 301  μ mol/L ( β 0.010, 95% CI 0.004–0.017;P = 0.002 ). The levels of IGF-1 SDS decreased with the elevation of UA when UA was either less than 168  μ mol/L ( β   −0.055, 95% CI −0.081–−0.028;P < 0.001 ) or more than 301  μ mol/L ( β   −0.005, 95% CI −0.013–0.002;P = 0.174 ). Conclusions . This study demonstrated a nonlinear relationship between IGF-1 and UA levels in Chinese children and adolescents with ISS. This finding suggests that either high or low levels of UA may have an adverse effect on IGF-1, whereas appropriate UA levels have a beneficial effect.